Epidemiology and clinical features of emergency department patients with suspected COVID‐19: Insights from Australia's 'second wave' (COVED‐4). (6th January 2021) - O'Reilly, Gerard M; Mitchell, Robert D; Mitra, Biswadev; Akhlaghi, Hamed; Tran, Viet; Furyk, Jeremy S; Buntine, Paul; Wong, Anselm; Gangathimmaiah, Vinay; Knott, Jonathan; Raos, Max; Chatterton, Erica; et al.
Abstract: Objective: The aim of the present study was to describe the epidemiology and clinical features of patients presenting to the ED with suspected and confirmed COVID‐19 during Australia's 'second wave'. Methods: The COVID‐19 ED (COVED) Project is an ongoing prospective cohort study in Australian EDs. This analysis presents data from 12 sites across four Australian states for the period from 1 July to 31 August 2020. All adult patients who met the criteria for 'suspected COVID‐19' and underwent testing for SARS‐CoV‐2 in the ED were eligible for inclusion. Study outcomes included a positive SARS‐CoV‐2 test result, mechanical ventilation and in‐hospital mortality. Results: There were 106 136 presentations to the participating EDs and 12 055 (11.4%; 95% confidence interval [CI] 11.2–11.6) underwent testing for SARS‐CoV‐2. Of these, 255 (2%) patients returned a positive result. Among positive cases, 13 (5%) received mechanical ventilation during their hospital admission compared to 122 (2%) of the SARS‐CoV‐2 negative patients (odds ratio 2.7; 95% CI 1.5–4.9, P = 0.001). Nineteen (7%) SARS‐CoV‐2 positive patients died in hospital compared to 212 (3%) of the SARS‐CoV‐2 negative patients (odds ratio 2.3; 95% CI 1.4–3.7, P = 0.001). Strong clinical predictors of the SARS‐CoV‐2 test result included self‐reported fever, sore throat, bilateral infiltrates on chest X‐ray, and absence of a leucocytosis on first ED blood tests ( P < 0.05). Conclusions: In this prospective multi‐site study during Australia's 'second wave', a substantial proportion of ED presentations required SARS‐CoV‐2 testing and isolation. Presence of SARS‐CoV‐2 on nasopharyngeal swab was associated with an increase in the odds of death and mechanical ventilation in hospital. Abstract : In this prospective multi‐site study during Australia's 'second wave', a substantial proportion of ED presentations required SARS‐CoV‐2 testing and isolation. The presence of SARS‐CoV‐2 on nasopharyngeal swab was associated with an increase in the odds of death and mechanical ventilation in hospital.